Design of Quadratic Optimal Regulator System for State Space Model of Single phase Inverter both in Standalone and Gridtie Modes - Nagulapati Kiran; V.Anil Kumar; Dhanamjaya Appa Rao (Institute of Advanced Engineering and Science, 2014)
Since in 3-phase systems, the reliability of 3-phase Inverter is not good, under such situations Paralleled Inverter Systems are used. Parallel Inverter operation has a major role in uninterruptible power system (UPS) applications. Most of the standalone inverter systems use a LC filter and proportional-integral (PI) controller in their control loops. When connecting the paralleled inverters to utility grids, the capacitor becomes redundant and thus either a pure inductor or an LCL filter can be used as inverter output stage. Compared with the L filter, the LCL filter is more attractive because it cannot only provide higher harmonics attenuation with same inductance value, but also allow inverter to operate both in standalone and grid-tie modes, which makes it a universal inverter for distributed generation applications. Output of Inverter should always be checked. In this paper State Space Model of Single phase Inverter is analysis in two modes which are: a) Grid-tie Mode b) Standalone Mode.A Quadratic Optimal Regulator System is designed and its unit step response is obtained to validate whether the whole system (inverter system along with designed QOR) is a stable system or not. This is done using MATLAB Program.